P-265 Validation of the Epigenetic Reader and Histone Acetyltransferase BRD4 as a Therapeutic Target in a Murine Colitis Model. (February 2017) - Tian, Bing; Villeger, Romain; Liu, Ziqing; Chen, Haiying; Zhou, Jia; Pinchuk, Irina; Brasier, Allan
Abstract : Background: Long term persistence of chronic inflammation in ulcerative colitis (UC) is among the major factors contributing to neoplastic transformation and the development of colitis-associated colorectal cancer (CAC). The master regulator of innate immune response, NFkB, is a signal integrator that plays a critical role in the initiation and chronicity of UC mucosal inflammation. Upon its activation by phosphorylation and acetylation, NFkB triggers early inflammatory gene expression by recruiting bromodomain-containing protein 4 (BRD4) to inflammatory IL-6 and TNF-a genes whose enhanced expression produce recruitment, hyperactivation of effector immune cells and disruption of the epithelial barrier. We have previously shown that BRD4 is required for stabilization of NFkB binding on the promoters of inflammatory genes, activation of RNA polymerase II, and histone H3 Lys (K) 122 acetylation (H3K122Ac) to permit high levels of inflammatory gene expression by sentinel epithelial cells and stromal fibroblasts. Here, we hypothesized that this signaling pathway is critical to the inflammatory responses during UC development and evaluated the therapeutic effect by inhibiting BRD4 activity in a murine colitis model. Methods: We have used medicinal chemistry approaches to identify 2 novel small molecule BRD4 inhibitors, with nanomolar IC50 values and high specificity for BRD4. Dextran Sulfate (DSS)-induced acute colitis, a treatment which mimics the initiation of UC, was induced in WT (C57BL/6) mice by the addition of 3% DSS in the drinking water for 7 days. DSS treatment was conducted in the absence or presence of ZL-0420 and ZL-0454 administered by daily i.p. injection (50 mg/kg). Colonic tissue was examined for NFkB-BRD4 pathway activation by immunofluorescence microscopy; overall pathological changes (H&E stain followed by histological analysis) and inflammatory cytokine production by qRT-PCR. Results: There was no evidence of toxicity found due to DSS or BRD4 inhibitor treatment during the study period (7 d). DSS treatment with BRD4 inhibitors produced a significant reduction in the inflammatory score. In particular, we observed a marked decrease in lymphocytic infiltration and partial restoration of the colonic mucosa architecture. Further, BRD4 inhibitor resulted in a significant decrease (∼80%–90%) in a UC key inflammatory cytokine IL-6 by the colonic mucosa. The levels of NFkB and BRD4 activation were also compared between treatment groups using immunofluorescence staining of NFkB/RelA translocation, phospho-Ser276 RelA formation and induction of the BRD4 marker H3K122Ac. The BRD4 inhibitors reduced the DSS induction of the NFkB-BRD4 pathway in colon tissue, demonstrating target specificity in vivo. Conclusions: Our data suggest that BRD4 activation is critical to the initiation of the inflammation during UC. Furthermore, inhibition of the BRD4 activation is an attractive target for the development of novel UC therapy and in prevention of CAC. Using our novel BRD4 inhibitors, we will further seek to evaluate the effect of long-term BRD4 inhibition on UC-induced neoplastic transformation and development of CAC.